Particle stabilized foams using sustainable materials
Patent Information
- Application Number
- CN202610956300.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2018-07-03
- Filing Date
- 2019-07-01
- Publication Date
- 2026-09-18
AI Technical Summary
这些泡沫显示出高稳定性,但也需要大量的表面活性剂
[0085] Therefore, porous products, including those with surface-modified, i.e., hydrophobic particles according to the invention, are characterized by several ecological and economic advantages in the field of building materials, such as high thermal insulation capacity due to significantly low thermal conductivity, very high compressive strength, and flame retardancy resulting from the inorganic properties of the particles. In fact, they can easily withstand temperatures up to 1000°C. Moreover, porous products are waterproof and insensitive to moisture. All these features are achieved using extremely low-cost raw materials, as most foams can be made from waste materials or widely available natural materials used as raw materials. Therefore, these novel foams have great potential as thermal or acoustic insulation materials due to their low cost, good mechanical properties, and excellent thermal insulation performance. Furthermore, their environmental footprint aligns with recent and upcoming government initiatives: non-toxic, flame-retardant, fossil fuel-free, and with very low CO2 emissions generated during their production and operation. In addition to these attractive economic and technical aspects, the performance of these foams is customizable, depending on locally available resources, such as fly ash or soil particles of varying compositions. The density, pore size, porosity, and modifiers of foam can be adjusted to regulate mechanical properties and thermal conductivity, thus enabling the production of large product templates through a single technology.
Smart Images

Figure CN122771676A_ABST
Abstract
Description
[0001] This application is a divisional application of patent application No. 201980043422.8 filed on July 1, 2019, entitled "Particle-Stabilized Foam Using Sustainable Materials". Technical Field
[0002] This invention relates to the field of foam formation. Background Technology
[0003] By 2030, modern insulation materials are expected to reduce total energy costs by 20%. However, today's modern solutions must also adapt to evolving regulations, such as the use of non-flammable, non-toxic, and environmentally friendly materials. Currently, many major industry players are unable to meet these requirements. Polymer solutions such as expanded polystyrene (EPS) or polyurethane (PU), despite being produced through toxic processes and being highly flammable, are most commonly used due to their low thermal conductivity. Other solutions, such as glass wool or mineral wool, are non-flammable but consume significant amounts of energy during manufacturing and can potentially cause human health problems. Recent solutions such as porous cement or aerogels tend to achieve low thermal conductivity while being flame-retardant and non-toxic during their manufacturing. However, the former option has high CO2 emissions, and aerogels remain very expensive. This has resulted in a gap in the building insulation market that is not being filled by currently available solutions.
[0004] Furthermore, a fairly simple and relatively inexpensive production method for lighter-density products has been achieved through foamed concrete (which is typically composed of a slurry of cement, sand, and water, which is then further mixed with aerated foam). The foam is formed using a foaming agent.
[0005] Against this backdrop, US2017158568 A1 and WO 2017 / 093796 A1 each disclose a method for producing ultralight mineral foam, wherein a Portland cement slurry is mixed with an aqueous foam comprising water and a foaming agent. This yields a foamed cement slurry, which is then subjected to casting.
[0006] Furthermore, EP 1 960 097 B1 discloses the manufacture of porous articles, such as cement-based wet foams, wherein the wet foam is prepared from a foamed suspension comprising colloidal particles. The surface of the particles has been modified with a short-chain surfactant. These foams exhibit high stability but also require large amounts of surfactant. Moreover, further processing of these foams (such as sintering) results in considerably high carbon dioxide emissions. Summary of the Invention
[0007] Therefore, the object of the present invention is to overcome the shortcomings of the prior art. In particular, one object is to provide a method for preparing foam, which is particularly improved in terms of environmental aspects.
[0008] This objective is achieved by the method according to claim 1. In particular, a method for preparing foam is provided, the method comprising the following steps:
[0009] - Provides a suspension comprising an aqueous liquid, preferably water, particles, and at least one surfactant, wherein the at least one surfactant at least partially hydrophobizes the surface of the particles; and
[0010] - To foam a suspension comprising particles having at least a partially hydrophobic surface. At least one surfactant is selected from surfactants having a backbone comprising at least nine carbon atoms.
[0011] A key issue is the stability of bubbles entering a foamed suspension before foam solidification. Traditionally, surfactants such as lipids and proteins are used to slow bubble coalescence by adsorption at the gas-liquid interface. However, these surfactant stabilization methods only stabilize the foam for a few hours due to the low adsorption energy of surfactants at the interface. Here, foam stability comes from the stabilizing effect of particles with at least partially hydrophobic surfaces, namely, stabilization due to the adsorption of surface-modified particles on the bubble surface and stabilization due to the formation of a percolation network of particles throughout the aqueous liquid. In contrast to conventional surfactants, these particles are kinetically trapped on the bubble surface, thereby increasing stability from days to months. Furthermore, the use of surfactants with a backbone comprising at least nine carbon atoms (referred to herein as long-chain surfactants) not only generates foam stabilization through particles present at the gas-liquid interface but also ensures the stability of the resulting wet foam through a robust percolation network formed around the bubbles generated during suspension foaming. The percolation network can be viewed as a gelling or reinforcement of the gas-liquid interface and the surrounding aqueous medium, which, in the present case, increases foam stability. The term "percolation network" is well-known in the prior art and can be referred to as "a percolation network of modified particles that forms a gel with an elastic modulus higher than its viscous modulus." Therefore, the gas-liquid interface is stabilized by a composite material of surface-modified particles thus formed, comprising a network interconnected with the modified particles. Typically, percolation networks are based on any type of surface-active particles and active molecules. Active particles correspond to particles whose surfaces can be modified by adsorption of molecules (such as surfactants), or particles that can be adsorbed at the gas-liquid interface without any surface modification. Active molecules are molecules (such as surfactants) that can be adsorbed onto the particle surface or at the gas-liquid interface.
[0012] Furthermore, if long-chain surfactants (i.e., surfactants with a backbone consisting of fewer than nine carbon atoms) are used instead of short-chain surfactants, the amount of surfactant required to stabilize both particles and foam is significantly reduced. In fact, it has been found that to achieve a porosity level comparable to that obtained using short-chain surfactants, the concentration of long-chain surfactants required is approximately four times lower or even less. This reduction in the amount of long-chain surfactant required to obtain stable foam is due to the fact that long-chain surfactants are more effective at modifying particle surfaces. In other words, less surfactant is needed to achieve the same degree of particle modification, i.e., hydrophobicity, compared to short-chain surfactants. Moreover, from surfactants of a certain molecular weight (typically around 300 g / mol), long-chain surfactants can further increase foam stability by participating in network formation by binding some particles together. That is, additional stability is achieved through particles interacting with each other via long-chain surfactants adsorbed on the particle surface.
[0013] In this context, the longest column of covalently bonded atoms in the continuous chain that together forms the structure of a surfactant molecule is referred to as the backbone. Thus, the backbone of a surfactant having a backbone comprising at least nine carbon atoms may include at least nine carbon atoms covalently linked to each other, or at least nine carbon atoms covalently linked to other atoms. Surfactants correspond to amphiphilic compounds known to those skilled in the art, meaning they comprise both hydrophobic and hydrophilic groups. Depending on the type of surfactant, by adding an amphiphilic surfactant to a suspension comprising particles, the surface of initially hydrophobic or hydrophobic particles may be made more hydrophilic or hydrophobic, respectively, and the surface of initially hydrophilic or hydrophilic particles may be made more hydrophobic or hydrophobic, respectively. The terms “hydrophobic,” “liquid,” “hydrophilic,” and “liquid” as used herein have meanings corresponding to their generally known meanings. For example, hydrophilic / liquid-sensitive means readily dispersed by water / solvent or readily absorbs water / solvent, while hydrophobic / liquid-sensitive means the opposite. Due to the fact that a surfactant has a backbone of at least nine carbon atoms, the particle will become hydrophobic upon interaction with the surfactant.
[0014] Amphiphilic surfactants can also be considered as comprising a tail and a head group, wherein preferably the tail has a main chain comprising at least nine carbon atoms. That is, at least one surfactant used herein corresponds to a molecule having a preferred polar head group and at least one hydrophobic chain, said main chain, wherein the polar head group interacts with the particles.
[0015] The strength of the percolation network at the gas-liquid interface and / or the strength of the percolation network formed throughout the continuous phase can be modulated by the type of particles with at least partially hydrophobic surfaces and the type of long-chain surfactants that interconnect different particles and adsorb at the gas-liquid interface. As a general trend, it has been observed that the longer the surfactant chain, the more likely it is to form a gel-like structure.
[0016] Additives such as polysaccharides, proteins, or other preferred organic molecules can be added to the suspension, and these additives then participate in network stabilization. That is, it has been observed that adding such compounds to suspensions comprising surface-modified particles, i.e., hydrophobic particles, results in improved foam stability and printability. This is attributed to the formation of a gel-like structure. Additives conceivable in this context include cellulose, xanthan gum, or fumed silica.
[0017] In this regard, it should be noted that a first suspension comprising an aqueous liquid, preferably water, and at least one surfactant can be prepared, and then particles can be added to the first suspension, wherein the at least one surfactant at least partially hydrophobizes the surface of the particles, thereby preparing a second suspension, which is then foamed. Similarly, a first suspension comprising an aqueous liquid and particles can be prepared, and then at least one surfactant can be added to the first suspension to form a second suspension, which is then foamed. Furthermore, it should be noted that it is also conceivable to prepare a suspension comprising an aqueous liquid and particles, and another suspension comprising an aqueous liquid and a surfactant, and then mix the two suspensions, wherein the mixture corresponds to the suspension undergoing foaming in the context of this application. All statements herein relating to one of these preparation methods are applicable to the other methods of preparation with necessary modifications to the details.
[0018] The aqueous liquids used to prepare the suspensions or the first and second suspensions are water-based and may be water alone or a mixture, such as, for example, a mixture of water and an alcohol. The water may be untreated water, drinking water, purified water, or distilled water. Alcohols that are conceivable are fatty alcohols, preferably ethanol. For example, it is conceivable to use a mixture comprising about 30 to 40 vol% ethanol and about 60 to 70 vol% water per total volume of the mixture.
[0019] Preferably, at least one surfactant is selected from the group consisting of polyelectrolytes, proteins, polysaccharides, glycerol, glycerides (such as monoglycerides, diglycerides, and triglycerides), fatty acids (such as oleic acid or linoleic acid), ammonium compounds, alkyl compounds, or combinations thereof. That is, the surfactant used in the suspension to at least partially hydrophobize the particle surface can be a polyelectrolyte and / or a protein and / or a polysaccharide and / or glycerol and / or glycerides and / or fatty acids and / or ammonium compounds and / or alkyl compounds, in each case, the surfactant comprising a backbone comprising at least nine carbon atoms.
[0020] When at least one surfactant is a polysaccharide, a conceivable polysaccharide compound is deacetylated chitosan. A conceivable triglyceride is Miglyol® 812, and Imwitor® 988 are examples of conceivable monoglycerides and diglycerides, respectively. When at least one surfactant is a polyelectrolyte, conceivable polyelectrolytes are, for example, polyacrylic acid, polystyrene sulfonate, and polyallylamine hydrochloride.
[0021] The polyelectrolytes in the suspension can be anionic, cationic, or zwitterionic, and / or the proteins in the suspension can be anionic, cationic, nonionic, or zwitterionic, and / or the polysaccharides in the suspension can be anionic, cationic, nonionic, or zwitterionic.
[0022] The polyelectrolyte and / or protein and / or polysaccharide and / or glycerol and / or glyceryl ester and / or fatty acid and / or ammonium compound and / or alkyl compound preferably have at least one group selected from bromides, amines, phosphate esters, phosphonates, sulfates, amides, carboxylic acids, pyrrolidines, betaines, or gallates or their corresponding salts. In this case, the group selected from bromides, amines, phosphate esters, phosphonates, sulfates, amides, carboxylic acids, pyrrolidines, betaines, or gallates or their corresponding salts corresponds to the aforementioned head of the amphiphilic surfactant.
[0023] Gallic ester compounds that can be thought of are lauryl gallate, betaine compounds that can be thought of are cocamidopropyl betaine, and ammonium compounds that can be thought of are primary, secondary or tertiary amine compounds, wherein one or more substituents are preferably alkyl or aryl groups respectively.
[0024] Polyelectrolytes correspond to macromolecules with anionic, cationic, or zwitterionic dissociable groups, as they are known in the art. These groups dissociate in aqueous solutions (such as water), giving the macromolecules a charged state. Polyelectrolytes can be classified as weak or strong, with strong polyelectrolytes being charged polyelectrolytes whose charge is independent of the pH of the aqueous solution, while weak polyelectrolytes are polyelectrolytes whose degree of dissociation depends on the pH of the aqueous solution. It is conceivable to use both types of polyelectrolytes as surfactants.
[0025] At least one surfactant is preferably a glyceryl monostearate compound (particularly preferred Cremodan). TM SE019 is commercially available from Danisco. TM ingredients, cetyltrimethylammonium bromide (CTAB), tetradecyltrimethylammonium bromide (TTAB), or nonylamine (CH3(CH2)7CH2NH2).
[0026] In the case of glyceryl monostearate (also known as 2,3-dihydroxypropyl octadecanoate, and a glyceryl ester of stearic acid), the glyceryl ester corresponds to the head of the amphiphilic surfactant, while the hydrocarbon chain attached to the glyceryl ester corresponds to the tail of the amphiphilic surfactant. Similarly, in the cases of CTAB and TTAB, ammonium bromide corresponds to the head of the surfactant, while the hydrocarbon chain corresponds to the tail of the surfactant. Furthermore, in the case of nonylamine, the amino group corresponds to the head of the surfactant, while the hydrocarbon chain corresponds to the tail of the surfactant.
[0027] It should be noted that these compounds, typically long-chain surfactants, can be provided alone or in mixtures of various surfactants and / or other compounds. For example, in Cremodan... TM In the case of monostearate compounds in the form of SE 019, a mixture including monostearate compounds and locust bean gum, sodium alginate, guar gum, and carrageenan is added. Similarly, to at least partially hydrophobize the surface of the particles in the suspension, one type of surfactant or two or more different types of surfactants can be used simultaneously or subsequently. For example, surface hydrophobization can be accomplished by adding only hexadecyltrimethylammonium bromide or nonylamine to the suspension. However, it is also conceivable, for example, to add a mixture of hexadecyltrimethylammonium bromide and nonylamine and tetradecyltrimethylammonium bromide to the suspension.
[0028] With Cremodan TMOne of the advantages of using monostearate compounds as surfactants is their non-toxicity. In fact, environmentally friendly materials can be manufactured using such non-toxic surfactants.
[0029] Similarly, it is conceivable to use one or more proteins or mixtures of proteins as surfactants, with non-toxic proteins such as gelatin, bovine serum albumin or casein being preferred.
[0030] At least one surfactant may be present in an amount of from about 0.001 wt% to about 5 wt% per particle's total weight, preferably in an amount of from about 0.01 wt% to about 2 wt% per particle's total weight. Therefore, it should be noted that, with respect to the particularly preferred surfactants described above, the preferred amounts are nonylamine (from about 0.001 wt% to about 5 wt% per particle's total weight), CTAB (from about 0.001 wt% to about 5 wt% per particle's total weight), TTAB (from about 0.001 wt% to about 5 wt% per particle's total weight), and Cremodan (from about 0.001 wt% to about 5 wt% per particle's total weight). TM The particularly preferred amount depends on the nature and composition of the particles. For example, it is particularly preferred to use about 0.09% by weight of TTAB per particle's total weight. Similarly, it is particularly preferred to use about 1.15% by weight of Cremodan per particle's total weight. TM CTAB at approximately 0.09% by weight per particle and nonylamine at approximately 0.09% by weight per particle or approximately 0.04% by weight per suspension.
[0031] One or more additives may be added to the suspension, and the additives may be selected from:
[0032] - Stabilizer,
[0033] - Plasticizers
[0034] - High-efficiency water-reducing agent (superplasticizer, also known as water-reducing agent, super plasticizer or strong plasticizer).
[0035] - Retarder,
[0036] - Accelerator,
[0037] - Adhesive,
[0038] - Wetting agent,
[0039] - Gas generating agent,
[0040] - Hardener, and
[0041] - Rheology modifiers.
[0042] Furthermore, if the two suspensions are prepared as described above, one or more of the additives can be added to the first and / or second suspensions before the second suspension is foamed, and / or one or more of the additives can be added to the second suspension after the second suspension has been foamed. These additives are commonly used in the manufacture of building materials and are therefore known to those skilled in the art.
[0043] For example, conceivable stabilizers for limiting cracking in the final porous products produced from foams (such as cement) are cellulose compounds, such as cellulose microfibers, methylcellulose, hydroxypropyl cellulose, or microcrystalline cellulose (such as Vivapur). TM (A mixture of microcrystalline cellulose and sodium carboxymethyl cellulose). Furthermore, these agents are also used to increase foam stability. Preferably, one or more stabilizers are used in an amount of about 10% by weight of the total weight of each particle, more preferably about 4% by weight of the total weight of each particle, more preferably about 2% by weight of the total weight of each particle, and particularly preferably about 0.1% by weight of the total weight of each particle.
[0044] To reduce the viscosity of the suspension, plasticizers and / or high-efficiency water-reducing agents, such as lignin sulfonates, naphthalene, melamine, or polycarboxylic acid polymers, such as sulfonate-based naphthalene, sulfonate-based melamine, or polycarboxylic acid ethers, can be used.
[0045] The setting time can be adjusted, for example, by using retarders (such as lignin sulfonates, hydroxycarboxylic acids and their salts, phosphonates, sugars, phosphates, borates and salts of lead, zinc, arsenic or antimony), and / or by using accelerators (such as calcium chloride, potassium chloride, sodium silicate, alkali metal hydroxides or calcium aluminate).
[0046] Shrinkage or cracking can be prevented by using adhesives, such as polymers, especially polyvinyl acetate (PVAc), polyvinyl alcohol (PVA), polyethylene glycol (PEG), or starch.
[0047] Wetting agents such as alcohols, oils, or glycols can be used to alter the contact angle and to promote the adsorption of particles at the gas-liquid interface.
[0048] If in-situ foaming is required, a gas generator, such as aluminum powder or hydrogen peroxide, can be added.
[0049] Contemplated hardeners include hydraulic binders, such as cement, especially Portland cement, or alkaline solutions, such as alkali metal hydroxides (e.g., NaOH, KOH) with sodium silicate or potassium silicate (Na₂SiO₃, K₂SiO₃). 3、A mixture of Na₂O•SiO₂ and K₂O•SiO₂. For this purpose, the hardener is preferably used in an amount of up to 50% by volume, more preferably up to 40% by volume, and particularly preferably up to 30% by volume. Regarding alkaline solutions, especially sodium silicate, it should be noted that the compound undergoes geopolymerization with the surface-modified particles via a condensation reaction, where this specific reaction process results in very low CO₂ emissions. The use of cement has the advantage of being able to harden at ambient temperatures, but this process generates CO₂.
[0050] In addition, rheology modifiers such as fumed silica, cellulose, clay, salt-insensitive superabsorbents (such as poly(acrylamide-co-acrylic acid)) or combinations thereof can be used. This is particularly useful if the foam subsequently undergoes extrusion or 3D printing, as described below. In this context, the rheology modifier is used for the purpose of improving the printability of the foam, wherein the printability improver can be added to the optionally foamed suspension. It has been observed that adding a small amount of clay to a fly ash mixture significantly improves the printability of the foam. The amount of printability improver conceivable is up to about 30% by weight per particle, preferably up to about 10% by weight per particle. For example, if it is an ash-based foam, the preferred amount of fumed silica is in the range of about 1 to 5% by weight per particle, the preferred amount of cellulose is in the range of about 0.1 to 3% by weight per particle, and the preferred amount of clay can be up to 30% by weight per particle.
[0051] As described above, the surface modification of particles, i.e., the hydrophobicization of particles, is achieved through the physical and / or chemisorption of amphiphilic surfactants on the particle surface. The pH of the suspension depends on the type and amount of particles used. Furthermore, lower or higher pH conditions are preferred depending on the charge of the surface to be coated by the surfactant and, consequently, the charge of the surfactant. Therefore, it may be necessary to adjust the pH of the suspension to create the optimal chemical environment for surface modification, foaming, or further processing of foams, respectively.
[0052] Before or after foaming the suspension, the pH value of the suspension can be adjusted to approximately 3 to 14, preferably to approximately 8 to 14. Depending on the composition of the particles, a specific pH value will result in better surfactant adsorption at the particle interface. For example, alumina (Al₂O₃) particles are positively charged at pH values of 3 to 7. Therefore, under these conditions, negatively charged surfactants are preferred because they enhance the adsorption of negatively charged surfactants on positively charged particles. Similarly, improved interaction is obtained, for example, between silica particles and positively charged surfactants. Or in other words, good electrostatic adsorption of the surfactant on the particle surface can be achieved if the surfactant and particles have opposite charges. The preferred pH value is then the pKa value, i.e., the logarithmic acid dissociation constant of the surfactant. The pH value can be adjusted by adding alkaline or acidic compounds or solutions to the suspension. For this purpose, hydrochloric acid (HCl) and sodium hydroxide (NaOH) are commonly used to adjust the pH value.
[0053] Preferably, the particles are charged particles. It should be noted that, due to the surface hydroxyl groups reacting with protons or hydroxyl anions (OH-) present in the aqueous phase... - The reaction between the particles can include a net negative charge or a net positive charge on the particle surface, even if the total charge of the permeation network is neutral.
[0054] The particles can be inorganic particles, preferably selected from aluminosilicates or calcium silicates, especially inorganic particles obtained from mineral processing tailings, catalyst residues, coal bottom ash, rice husk ash, palm oil ash, waste glass, papermaking sludge ash, sludge from water treatment, mica, vermiculite, microsilica, ground granular blast furnace slag (GGBS), pigments (such as titanium dioxide TiO2), perlite, or ceramic waste.
[0055] Particularly preferred are particles comprising fly ash and / or soil particles. Other conceivable examples of aluminosilicates are kaolin and feldspar.
[0056] Fly ash is a heterogeneous material, primarily composed of silicon dioxide (SiO2), aluminum oxide (Al2O3), iron oxide (Fe2O3), and less commonly, calcium oxide (CaO). Soil particles, also known as clay particles, are similarly heterogeneous materials, combining one or more clay minerals with possible trace amounts of quartz (SiO2) and metal oxides (such as aluminum oxide (Al2O3) and magnesium oxide (MgO)). Clay minerals are compounds primarily composed of silicon dioxide (SiO2), aluminum oxide (Al2O3), iron oxide (Fe2O3), and alkali metal oxides (such as potassium oxide (K2O) and sodium oxide (Na2O)).
[0057] That is, particularly preferably, the particles representing the foam base are aluminosilicates, preferably fly ash or soil, i.e., clay particles. Furthermore, it is preferred to use any one of these particles or a combination thereof. However, the use of other inorganic wastes, such as the compounds mentioned above, is also conceivable. These wastes can also be referred to as secondary raw materials. Preferably, the particles are untreated particles, such as fly ash particles taken from coal combustion waste. These particles can be used directly to manufacture foam without the need for a purification process.
[0058] Furthermore, the particles can also be obtained by recycling previously prepared (e.g., prepared by the method according to the invention) finalized porous articles, wherein the finalized porous articles are crushed to produce particles, which are then reused in the new preparation of foam according to the invention. In doing so, the binder phase, i.e., cement, geopolymer, etc., is hydrated during the consolidation process and used as inert particles. Since some of the surfactant evaporates during the drying process, more surfactant may be required to prepare stable foam from this recycled material.
[0059] Furthermore, regarding the toxicity of these particles, it should be noted that fly ash is widely used in the construction industry as an additive in concrete, where trace amounts of heavy metals may be present depending on the source of the ash. However, by using hardeners such as cement or sodium silicate, a reaction occurs between the hardener and the fly ash particles, producing calcium silicate hydrates or geopolymers. As a result, any trace heavy metals are trapped in these newly formed matrices, thereby minimizing or even preventing the release of heavy metals into the environment.
[0060] The particle size corresponds to the average particle size measured for the maximum size and depends on the source of the particles. In the case of fly ash, for example, fly ash particles are typically spherical in shape, with a size range of about 0.5 µm to about 300 µm. However, it is generally preferred that the particles have a size between about 1 nm and about 100 µm, preferably between about 200 nm and about 50 µm. If desired, the particle size can be adjusted by sieving or ball milling techniques commonly known in the art.
[0061] According to the present invention, the foamable suspension comprises:
[0062] - Aqueous liquid, preferably water.
[0063] - Particles with at least partially hydrophobic surfaces obtained by the above method, and
[0064] - One or more additives selected from stabilizers, plasticizers, super water-reducing agents, retarders, accelerators, binders, wetting agents, gas generators, hardeners and rheology modifiers.
[0065] The aqueous liquid preferably corresponds to an aqueous liquid used to prepare a suspension comprising particles having at least a partially hydrophobic surface as described above. Furthermore, it is conceivable to add one or more of the above-described additives to the suspension or foamable suspension, respectively, prior to foaming. However, it is also possible to add one or more of the above-described additives to the aqueous liquid prior to adding the particles and surfactant.
[0066] According to the present invention, such a foamable suspension can be used to prepare foam, wherein the foamable suspension is mechanically foamed, preferably by a mixer, and / or wherein the foamable suspension is foamed in situ by adding a gas generator to the foamable suspension.
[0067] That is, gas can be incorporated into the foamable suspension containing particles with at least partially hydrophobic surfaces obtained by the above methods in any convenient manner, such as by direct foaming (e.g., mechanical mixing) or by using a gas generator (i.e., in situ, where a gas such as oxygen (O2) is generated in a chemical reaction). For convenience and economy, air is preferred. However, other gases, such as nitrogen, oxygen, argon, or carbon dioxide, are also conceivable. For this purpose, the foamable suspension can be subjected to high-speed agitation when exposed to the atmosphere. Agitation can be carried out by a mixer and continued for a sufficient time, during which bubbles are introduced into the foamable suspension until the desired expansion is achieved. Other ways of introducing gas into the foamable suspension include, for example, by bubbling gas into the foamable suspension through a filter or by injecting pressurized gas into the foamable suspension through a nozzle. By selecting the pore size of the filter or the diameter of the nozzle, the pore size of the foam can be adjusted, thereby adjusting the pore size of the final porous article prepared from the foam. In another technique, reactive gas-generating substances such as hydrogen peroxide (H₂O₂) or manganese oxide (MnO) can be added to a foamable suspension, where the generated gas causes the foamable suspension to foam. It should be understood that the more gas is incorporated into or generated in the foamable suspension, the greater the porosity of the resulting foam, with the porosity level depending on the particle size, particle type, and particle concentration. It should also be noted that the foam can only be generated within minutes, requiring no special treatment other than surface modification of the particles using long-chain surfactants, i.e., hydrophobication.
[0068] The foam according to the invention comprises a foamed suspension, the foamed suspension comprising:
[0069] - Aqueous liquid, preferably water.
[0070] - Particles with at least partially hydrophobic surfaces obtained by the above method, and
[0071] - One or more additives selected from stabilizers, plasticizers, super water-reducing agents, retarders, accelerators, binders, wetting agents, gas generators, hardeners and rheology modifiers.
[0072] The aqueous liquid comprising at least partially hydrophobic particles preferably corresponds to a suspension or foamable suspension comprising particles having at least partially hydrophobic surfaces as described above. Furthermore, it is conceivable to add one or more of the above-described additives to the suspension or foamable suspension, respectively, before and / or after foaming. However, it is also possible to add one or more of the above-described additives to the aqueous liquid before adding the particles and surfactant. Foaming of the suspension or foamable suspension can be carried out by mechanical foaming and / or in-situ foaming as described above.
[0073] Particles having at least partially hydrophobic surfaces preferably constitute at least about 50% of the total solid portion of the foam, particularly preferably about 80%, and / or the foam density is preferably about 10 kg / m³. 3 Approximately 1000 kg / m 3 Within the range, it is particularly preferred to be around 30 kg / m 3 Approximately 800 kg / m 3 Within the range of, and / or the foam preferably has a porosity of about 20 vol% to about 99 vol%, particularly preferably about 50 vol% to about 98 vol%, and / or the foam preferably has an electrical conductivity in the range of about 0.01 W / (mK) to about 0.3 W / (mK), particularly preferably about 0.02 W / (mK) to about 0.2 W / (mK), and / or the foam preferably includes bubbles with a size in the range of about 1 µm to about 1 mm, particularly preferably in the range of about 10 µm to about 100 µm.
[0074] It was found that the foam of the present invention remained stable for several weeks at a porosity level of, for example, 95% by volume, resulting in a foam density of 70 kg / m³. 3 Up to 600 kg / m 3Within a certain range. If the particles are ball-milled before surface modification with surfactants, this porosity level can be further increased to 90% by volume or even higher. Due to their high stability, foams can be combined with rheology modifiers (such as fumed silica) to obtain pastes that can be further processed under high shear conditions. As a result, they can be extruded or 3D printed in any shape and can be stored for several days. The mechanical properties of dried foams can be tuned by adding a hardener to the initial composition or the pre-foamed suspension. In construction engineering, the compressive strength of the product to be used is a critical performance. Typically, a compressive strength of at least about 50 kPa is required, with the foams according to the invention reaching an order of magnitude higher at at least about 500 kPa or even up to 1 MPa. Hardeners with concentrations below 20% (such as sodium silicate or Portland cement) can produce foams with compressive strengths in the range of 1 MPa, thus exceeding industrial requirements.
[0075] According to the present invention, a method for preparing porous materials includes the following steps:
[0076] - Provide the foam mentioned above,
[0077] - Casting, extrusion, or additive manufacturing, especially 3D printing of the foam, and
[0078] - Optional solidification, and / or
[0079] - Optional drying, and / or
[0080] - Optional sintering.
[0081] The subsequent processing of the foam will depend primarily on the properties of the expected porous product.
[0082] In principle, it is conceivable to subject the foam to hardening, sintering, or processing such as 3D printing, extrusion, or injection molding. Therefore, according to the invention, the foam described above can be used to produce porous articles, wherein the foam undergoes casting or extrusion or additive manufacturing, and optionally solidification and / or optional drying and / or optional sintering.
[0083] Different hardening options are conceivable, such as hardening the foam simply by air drying. However, it is also conceivable to add one or more of the aforementioned hardeners, such as cement or an alkaline solution (e.g., sodium silicate). Another hardening option is, for example, sintering the foam at a temperature in the range of about 800°C to 1800°C, preferably 900°C, for a period of about one to three hours, preferably about two hours.
[0084] If the foam is to undergo printing, it is conceivable, but not necessary, to add rheology modifiers or printability improvers, such as fumed silica, to the suspension separately before foaming. Subsequently, the suspension can be foamed, loaded into a cylinder, etc., and then discharged from an orifice or nozzle provided on the cylinder. The printing speed depends on the size of the orifice or nozzle. Preferably, the orifice or nozzle size is in the range of about 0.2 mm to about 400 mm, particularly preferably in the range of about 0.4 mm to about 200 mm. Different printing speeds can be obtained depending on the nozzle diameter. In the case of a smaller nozzle diameter, for example, about 0.4 mm, a printing speed of about 1 mm / s to 15 mm / s, preferably about 4 mm / s, can be achieved. In the case of a larger nozzle diameter, for example, about 200 mm, a printing speed of about 1 cm / s to 20 cm / s, preferably about 5 cm / s, can be achieved.
[0085] Therefore, porous products, including those with surface-modified, i.e., hydrophobic particles according to the invention, are characterized by several ecological and economic advantages in the field of building materials, such as high thermal insulation capacity due to significantly low thermal conductivity, very high compressive strength, and flame retardancy resulting from the inorganic properties of the particles. In fact, they can easily withstand temperatures up to 1000°C. Moreover, porous products are waterproof and insensitive to moisture. All these features are achieved using extremely low-cost raw materials, as most foams can be made from waste materials or widely available natural materials used as raw materials. Therefore, these novel foams have great potential as thermal or acoustic insulation materials due to their low cost, good mechanical properties, and excellent thermal insulation performance. Furthermore, their environmental footprint aligns with recent and upcoming government initiatives: non-toxic, flame-retardant, fossil fuel-free, and with very low CO2 emissions generated during their production and operation. In addition to these attractive economic and technical aspects, the performance of these foams is customizable, depending on locally available resources, such as fly ash or soil particles of varying compositions. The density, pore size, porosity, and modifiers of foam can be adjusted to regulate mechanical properties and thermal conductivity, thus enabling the production of large product templates through a single technology. Attached Figure Description
[0086] Preferred embodiments of the invention are described below with reference to the accompanying drawings, which are intended to illustrate the present preferred embodiments of the invention and not to limit the invention. In the drawings,
[0087] Figure 1 A schematic diagram of a method for preparing foam and porous articles according to a first embodiment is shown;
[0088] Figure 2 A schematic diagram of a method for preparing foam and porous articles according to a second embodiment is shown;
[0089] Figure 3 SEM images of foam containing fly ash particles are shown.
[0090] Figure 4 SEM images of foam containing soil particles are shown;
[0091] Figure 5 Another SEM image of foam containing fly ash particles is shown;
[0092] Figure 6 Another SEM image showing foam containing soil particles is shown;
[0093] Figure 7 The image shows foam containing soil particles;
[0094] Figure 8 An image of foam containing fly ash particles is shown;
[0095] Figure 9a shows a schematic diagram of the gas-liquid interface in a foam according to the present invention;
[0096] Figure 9b shows an enlarged view of the gas-liquid interface according to Figure 9a, where the established percolation network is evident. Detailed Implementation
[0097] exist Figure 1 and 2 The text describes different methods for preparing foams and porous products. In fact, in... Figure 1 In the process, a particle-stabilized foam is prepared by producing a first suspension comprising an aqueous liquid and particles in the first step. For example, approximately 40% by weight of soil particles or approximately 50% by weight of fly ash particles per total weight of the suspension can be added to the water. In the second step, a surfactant having a backbone comprising at least nine carbon atoms is added to the suspension to at least partially hydrophobize the surface of the particles. For example, Cremodan can be added in an amount of approximately 0.72% by weight of the total weight of the suspension. TMIn addition, additives for adjusting or improving mechanical properties can be added to the suspension. For example, stabilizers such as cellulose compounds can be added to resist cracking, network stabilizers such as proteins or polysaccharides to improve mechanical properties, and rheology modifiers such as fumed silica can be added. In one embodiment, approximately 0.5% by weight of hydroxypropyl cellulose, approximately 0.2% by weight of xanthan gum, and approximately 2% by weight of fumed silica per particle are added. In the third step, the suspension is stirred with a mixer to introduce air into the suspension. This forms a particle-stabilized foam. In this particular suspension composition, a particle-stabilized foam with a porosity of up to 98% is produced. In the fourth step, the particle-stabilized foam can be processed to form the desired porous article. For example, the particle-stabilized foam can be cured simply by air drying. For rapid curing, it is conceivable to add a curing agent to the particle-stabilized foam. For example, a dispenser can be used comprising a particle-stabilized foam stored in a first drum and a hardener, such as cement, stored in a second drum in an amount of approximately 2% to 20% by weight per total weight of the suspension, wherein both components are then extruded through a dual static mixer. In this case, the cement begins to react with water, thus initiating rapid setting. However, it is also conceivable to sinter or cast the particle-stabilized foam. In the former case, the particle-stabilized foam can be sintered at a temperature in the range of approximately 800°C to 1400°C for a time of approximately one to three hours, wherein the heating rate is approximately 0.5°C / min to approximately 5°C / min, and the cooling rate is set to approximately 10°C / min to 2°C / min. In the latter case, an additive, such as sodium silicate, can be added to the particle-stabilized foam in an amount of approximately 10% or 20% by weight per total weight of the suspension before casting the foam.
[0098] exist Figure 2 In this method, particle-stabilized foam is prepared by in-situ foaming using a gas generating agent. According to this method, a first solution comprising an aqueous liquid such as water and surface-modified particles is mixed with a second solution comprising a gas generating agent such as hydrogen peroxide. In this embodiment, the first solution further comprises a catalyst, such as manganese oxide (MnO) and sodium hydroxide (NaOH), and the second solution further comprises a hardener, such as sodium silicate or cement. Here, the two solutions are initially stored separately in two cylinders of a distributor and then discharged through a dual static mixer, thereby generating foam expansion.
[0099] exist Figure 3 and 4 The paper depicts granular-stabilized foams prepared using fly ash particles and soil particles, respectively. Specifically, Figure 3A foam comprising fly ash particles was described, wherein 58 wt% fly ash per total weight of suspension and 0.72 wt% Cremodan per total weight of suspension were initially used. TM A foamable suspension was prepared by adding 41.28% by weight of water per total weight of the suspension. After foaming the suspension, the foamed suspension was subjected to sintering at 900°C to obtain the desired product. Figure 3 The foam.
[0100] Figure 4 A foaming process involving soil particles was described, in which a foamable suspension was first prepared using 45 wt% soil particles, 0.04 wt% TTAB, and 54.96 wt% water per total weight of the suspension. The suspension was then foamed by mechanical foaming for 5 minutes. Figure 4 The image shown was taken after the foamed suspension had been dried for 3 days at ambient temperature.
[0101] Figure 5 A foam comprising fly ash particles was described, wherein a foamable suspension was first prepared using 58 wt% fly ash particles, 0.05 wt% TTAB, 34.75 wt% water, and 7.2 wt% sodium silicate (Na₂O•SiO₂) per total weight of the suspension. The suspension was then mechanically foamed and subsequently dried. The drying process included the following steps: i) drying at 40°C and 100% humidity for 24 hours, ii) drying at 40°C and 65% humidity for 6 days, and iii) drying at 25°C for 20 days.
[0102] Figure 6 A foam containing soil particles was depicted, comprising 45 wt% soil particles and 0.59 wt% Cremodan per wt% of the total suspension weight. TM The suspension consisted of 10% by weight of Portland cement and 44.41% by weight of water per liter of total weight. The suspension was then mechanically foamed and subsequently dried.
[0103] Figure 7 A foam comprising soil particles was depicted, wherein 45 wt% of soil particles, 0.04 wt% of nonylamine, 10 wt% of cement, and 44.96 wt% of water per total weight of suspension were mechanically foamed. The foam was then dried in an oven at 60°C. The foam of this embodiment exhibits small pore sizes, a result of a high mixing rate of 800 rpm applied during the foaming process. Two Swiss franc coins placed on top of the foam further illustrate the small pore size.
[0104] Figure 8 A foam comprising fly ash particles is depicted, which is generated by two solutions: a first solution and a second solution. The first solution comprises 68% by weight of fly ash particles per unit weight of the total weight of the first solution, and 0.4% by weight of Cremodan per unit weight of the total weight of the first solution. TM The first solution contains 0.1 wt% manganese oxide and 31.5 wt% water per wt% of the total weight of the first solution. The second solution contains 29.6 wt% sodium silicate (Na₂O•SiO₂), 14.9 wt% hydrogen peroxide (H₂O₂), and 55.5 wt% water per wt% of the total weight of the second solution. After the two solutions are mixed, foam is generated by in-situ gas generation and then solidified using sodium silicate. The resulting foam is then dried in a drying process comprising the following steps: i) drying at 40°C and 100% humidity for 24 hours, ii) drying at 40°C and 65% humidity for 6 days, and iii) drying at 25°C for 20 days. The resulting foam contains pores with a size of at most 1 to 2 mm. A Swiss franc coin placed on top of the foam further illustrates the large pore size.
[0105] These examples directly demonstrate that a much smaller amount of long-chain surfactant is required to achieve the same stability as foams produced by short-chain surfactants. In fact, referring, for example, to the foam prepared by 0.04 wt% nonylamine (with 9 carbon atoms in the main chain) per total weight of suspension, as shown in Figure 9, the required long-chain surfactant is reduced by more than an order of magnitude compared to a similarly stable foam prepared by approximately 2 wt% of propyl gallate per total weight of suspension.
[0106] Figures 9a and 9b illustrate schematic diagrams of the particle stabilization effect on bubbles formed in the foam according to the invention. As can be seen from these figures, surface-modified particles are adsorbed onto the surface of bubbles generated during the foaming of the foamable suspension by surfactants. Furthermore, the particles, whose long backbones are partially hydrophobic by the surfactants, form a percolation network around the bubbles and throughout the continuous liquid medium, which further increases the stability of the foam.
[0107] about Figure 1 , 2 9a and 9b should be noted; these compounds are not drawn to scale. In reality, the particle size is usually much larger than that of the surfactant.
[0108] Example 1: Mechanical foaming and addition of cement
[0109] Step 1: Optionally grind the aluminosilicate particles obtained from the secondary raw materials.
[0110] Step 2: Dissolve the long-chain surfactant in water.
[0111] Step 3: Optionally ground aluminosilicate particles are added to the dissolved long-chain surfactant, wherein the particles are dispersed by mixing at 200 revolutions per minute.
[0112] Step 4: Adjust the pH of the suspension from Step 3 to a pH of 9 to 10.
[0113] Step 5: Use a high-shear mixer to foam the suspension obtained in step 4 at 800 to 1000 revolutions per minute.
[0114] Step 6: Disperse the cement in the water.
[0115] Step 7: Use a high-shear mixer to mix the foamed suspension from Step 4 and the cement dispersed in water from Step 5 at 800 to 1000 revolutions per minute.
[0116] Step 8: Cast, extrude, or 3D print the foamed suspension mixed in Step 7.
[0117] Step 9: Allow the foamed suspension from Step 8 to solidify by covering it with or placing it in a humidity chamber at 70 to 100% humidity and 25°C for 4 to 7 days.
[0118] Step 10: Dry the porous product from step 9.
[0119] Example II: Mechanical foaming and addition of alkaline solution
[0120] Step 1: Optionally grind the aluminosilicate particles obtained from the secondary raw materials.
[0121] Step 2: Dissolve the long-chain surfactant in water.
[0122] Step 3: Optionally ground aluminosilicate particles are added to the dissolved long-chain surfactant, wherein the particles are dispersed by mixing at 200 revolutions per minute.
[0123] Step 4: Adjust the pH of the suspension from Step 3 to a pH of 9 to 10.
[0124] Step 5: Use a high-shear mixer to foam the suspension obtained in step 4 at 800 to 1000 revolutions per minute.
[0125] Step 6: Add sodium silicate solution (Na2O•SiO2) to the foamed suspension obtained in Step 5 by mixing using a high-shear mixer or by mixing using a dual static mixer with a single extruder, wherein the foamed suspension in Step 5 is contained in one cylinder and the sodium silicate solution is contained in another cylinder.
[0126] Step 7: Cast, extrude, or 3D print the suspension mixed in Step 6.
[0127] Step 8: Solidify the mixed suspension from Step 7 by covering it with a solution at 40 to 80°C, preferably 60°C, for 24 hours.
[0128] Step 9: Dry the porous product from Step 8.
[0129] Example III: In-situ foaming and alkaline solution
[0130] Step 1: Optionally grind the aluminosilicate particles obtained from the secondary raw materials.
[0131] Step 2: Dissolve the long-chain surfactant in water.
[0132] Step 3: Add the optionally ground aluminosilicate particles to the dissolved long-chain surfactant.
[0133] Step 4: Adjust the pH of the suspension from Step 3 to a pH of 9 to 10, and add a catalyst, such as manganese oxide (MnO).
[0134] Step 5: Prepare an alkaline solution using water and hydrogen peroxide (H2O2).
[0135] Step 6: Use a dual static mixer with a single screw extruder to mix the suspension from step 4 and the solution from step 5.
[0136] Step 7: Cast, extrude, or 3D print the suspension mixed in Step 6.
[0137] Step 8: Solidify the mixed suspension from Step 7 by covering it with a solution at 40 to 80°C, preferably 60°C, for 24 hours.
[0138] Step 9: Dry the porous product from Step 8.
[0139] Example IV: Mechanical foaming and sintering
[0140] Step 1: Optionally grind the aluminosilicate particles obtained from the secondary raw materials.
[0141] Step 2: Dissolve the long-chain surfactant in water.
[0142] Step 3: Optionally ground aluminosilicate particles are added to the dissolved long-chain surfactant, wherein the particles are dispersed by mixing at 200 revolutions per minute.
[0143] Step 4: Adjust the pH of the suspension from Step 3 to a pH of 9 to 10.
[0144] Step 5: Use a high-shear mixer to foam the suspension obtained in step 4 at 800 to 1000 revolutions per minute.
[0145] Step 6: Cast, extrude, or 3D print the foamed suspension from Step 5.
[0146] Step 7: Dry the porous product from Step 6.
[0147] Step 8: Depending on the particle composition, sinter the porous product dried in step 7 at a temperature between approximately 600°C and 1200°C for 2 hours.
Claims
1. A method for preparing foam, comprising the following steps: - Provides a suspension comprising an aqueous liquid, preferably water, particles, and at least one surfactant, wherein the at least one surfactant at least partially hydrophobizes the surface of the particles; and - To foam the suspension comprising the particles having at least partially hydrophobic surfaces. Its features are: - The at least one surfactant is selected from surfactants having a backbone comprising at least nine carbon atoms, preferably an amphiphilic molecule consisting of a tail attached to a head group, wherein the tail contains the backbone comprising at least nine carbon atoms, wherein the at least one surfactant is selected from the group consisting of polyelectrolytes, proteins, polysaccharides, glycerol, glycerides, fatty acids, ammonium compounds, alkyl compounds, or combinations thereof, and the polyelectrolyte and / or the protein and / or the polysaccharide and / or the glycerol and / or the glycerides and / or the fatty acids and / or the ammonium compounds and / or the alkyl compounds have at least one group selected from bromides, amines, phosphate esters, phosphonates, sulfates, amides, carboxylic acids, pyrrolidines, betaines, or corresponding salts; and - Add an alkaline solution to the suspension as a hardening agent, wherein the alkaline solution contains sodium silicate or potassium silicate.
2. The method according to claim 1, wherein the at least one surfactant is a glyceryl monostearate compound, hexadecyltrimethylammonium bromide, tetradecyltrimethylammonium bromide, nonylamine, or a combination thereof.
3. The method according to claim 1, wherein the alkaline solution undergoes a geopolymerization reaction with the surface-modified particles via a condensation reaction.
4. The method according to claim 1, wherein trace heavy metals present in the fly ash particles are trapped in the matrix formed by the reaction between the alkaline solution and the fly ash particles.
5. The method of claim 1, wherein a hydraulic binder is added to the suspension as an additional hardening agent.
6. The method of claim 1, wherein the at least one surfactant is present in an amount of about 0.001% by weight to 5% by weight per total weight of the particles, preferably in an amount of about 0.01% by weight to 2% by weight per total weight of the particles.
7. The method according to claim 1, wherein the particles comprise fly ash particles and / or soil particles.
8. The method according to claim 1, wherein the particles are inorganic particles selected from aluminosilicates or calcium silicates.
9. The method of claim 8, wherein the inorganic particles are obtained from inorganic waste and / or by recycling the ultimately consolidated porous article by crushing it to produce particles.
10. The method of claim 1, wherein one or more additives are added to the suspension, the additives being selected from: - Stabilizer, - Plasticizers - High-efficiency water-reducing agent - Retarder, - Accelerator, - Adhesive, - Wetting agent, - Gas generating agent, and - Rheology modifiers.
11. The method of claim 1, wherein the pH of the suspension is adjusted to about 8 to 14 before or after foaming the suspension.
12. A foamable suspension, comprising: - Aqueous liquid, preferably water. - Particles having at least a partially hydrophobic surface obtained according to any one of claims 1 to 11, - An alkaline solution is used as a hardening agent, wherein the alkaline solution contains sodium silicate or potassium silicate, and - One or more additives selected from stabilizers, plasticizers, super water-reducing agents, retarders, accelerators, binders, wetting agents, gas generators and rheology modifiers.
13. Use of the foamable suspension according to claim 12 for preparing foam, wherein the foamable suspension is mechanically foamed, preferably by a mixer, and / or The foamable suspension is foamed in situ by adding a gas generator to the foamable suspension.
14. A foam comprising a foamed suspension, said foamed suspension comprising: - Aqueous liquid, preferably water. - Particles having at least a partially hydrophobic surface obtained according to any one of claims 1 to 11, - An alkaline solution is used as a hardening agent, wherein the alkaline solution contains sodium silicate or potassium silicate, and - One or more additives selected from stabilizers, plasticizers, super water-reducing agents, retarders, accelerators, binders, wetting agents, gas generators and rheology modifiers.
15. The foam according to claim 14, wherein the particles having the at least partially hydrophobic surface constitute at least about 50% of the total solid portion of the foam, preferably about 80% of the total solid portion of the foam, and / or wherein the density of the foam is in the range of from about 10 kg / m 3 to about 1000 kg / m 3 , preferably in the range of from about 30 kg / m 3 to about 800 kg / m 3 , and / or The foam described above has a porosity of about 20 vol% to about 99 vol%, preferably about 50 vol% to about 98 vol%, and / or The foam described herein has an electrical conductivity in the range of about 0.01 W / (mK) to about 0.3 W / (mK), preferably in the range of about 0.02 W / (mK) to about 0.2 W / (mK), and / or The foam comprises bubbles with a size ranging from about 1µm to about 1mm, preferably from about 10µm to about 100µm.
16. A method for preparing a porous article, comprising the following steps: - Provide the foam according to claim 14 or 15, - Casting, extrusion, or additive manufacturing, especially 3D printing of the foam, and - Solidification, and / or - Optional drying, This causes the foam to harden in the presence of a hardener.
17. Use of the foam according to claim 14 or 15 for the production of porous articles, wherein the foam undergoes casting or extrusion or additive manufacturing and solidification and / or optional drying, such that the foam hardens in the presence of a hardener.
18. The use according to claim 17, wherein the porous article is a building material, a heat insulation or sound insulation material.
Citation Information
Patent Citations
Ultrastable particle-stabilized foams and emulsions
EP1960097B1
Ultra-light mineral foam and method for producing same
US20170158568A1
Ultra-light mineral foam
WO2017093796A1